Coffee Market Liberalisation and the Implications for Producers in Brazil, Guatemala and India - Russell, Bill; Mohan, Sushil; Banerjee, Anindya (Oxford University Press on behalf of the World Bank, 2014)
The standard approach to modelling the relationship between world and producer prices of coffee does not incorporate the effects of changing government policies and market structures. These changes have led to large structural breaks in the relationship between the prices implying the standard estimates are biased. We model coffee prices in Brazil, Guatemala and India allowing for the structural breaks and show that the liberalisation of coffee markets has benefited producers substantially both in terms of a higher share of the world price of coffee and higher real prices. This suggests that calls to re-regulate coffee markets may be misplaced.